2022
DOI: 10.1111/jgs.17833
|View full text |Cite
|
Sign up to set email alerts
|

Emergency and post‐emergency care of older adults with Alzheimer's disease/Alzheimer's disease related dementias

Abstract: Background The emergency department (ED) is a critical juncture in the care of persons living with dementia (PLwD), as they have a high rate of hospital admission, ED revisits, and subsequent inpatient stays. We examine ED disposition of PLwD compared with older adults with non‐dementia chronic disease as well as healthcare utilization and survival. Methods Medicare claims data were used to identify community‐dwelling older adults 66+ years old from 34 hospitals with either Alzheimer's disease/Alzheimer's dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…GEST uses a mixture of demographic, past medical, vital sign, lab, and healthcare utilization data. Among GEST variables, we note the importance of history of delirium or dementia, a finding that mirrors a recent study showing persons living with dementia have a higher risk of one‐year mortality following an ED visit as compared to individuals without dementia 36 . Similarly, though not often used as a prognostic marker in the ED, reticulocyte distribution width is associated with increased inpatient mortality, hospital readmission, and length of stay 37 .…”
Section: Discussionsupporting
confidence: 75%
“…GEST uses a mixture of demographic, past medical, vital sign, lab, and healthcare utilization data. Among GEST variables, we note the importance of history of delirium or dementia, a finding that mirrors a recent study showing persons living with dementia have a higher risk of one‐year mortality following an ED visit as compared to individuals without dementia 36 . Similarly, though not often used as a prognostic marker in the ED, reticulocyte distribution width is associated with increased inpatient mortality, hospital readmission, and length of stay 37 .…”
Section: Discussionsupporting
confidence: 75%
“…Emergency department visits for people with Alzheimer's or other dementias per 1,000 Medicare beneficiaries increased 28% between 2008 and 2018 (from 1,265 to 1,545), exceeding the increases in emergency department visits for individuals with cancer, ischemic heart disease and heart failure among others (Figure 14). 726 One group of researchers found that individuals with Alzheimer's or other dementias seen in the emergency department are more likely to be admitted to the hospital or nursing home from the emergency department than Medicare beneficiaries without Alzheimer's or other dementias 728 . Additionally, individuals with Alzheimer's or other dementias are more likely to have at least one hospitalization, have at least one subsequent emergency department visit, and be admitted to hospice in the 12 months following the initial emergency department visit.…”
Section: Use and Costs Of Health Care Long‐term Care And Hospicementioning
confidence: 99%
“…Without a standard strategy for cognitive screening in the ED, cognitive impairment in the absence of delirium would remain highly undetected, 3,5 as most patients identified as cognitively impaired in the 10‐CS did not have a previous dementia diagnosis or substantial cognitive complaints. Like delirium, cognitive impairment without delirium was associated with increased in‐hospital adverse events, prolonged LoS, and in‐hospital mortality, capturing risks beyond routine ED measures 1–3 . Although barriers exist (e.g., resource‐constrained settings and stressors related to acute illnesses), 9,10 our findings encourage broader cognitive screening for older patients in the ED.…”
Section: Discussionmentioning
confidence: 69%
“…Like delirium, cognitive impairment without delirium was associated with increased in-hospital adverse events, prolonged LoS, and in-hospital mortality, capturing risks beyond routine ED measures. [1][2][3] Although barriers exist (e.g., resource-constrained settings and stressors related to acute illnesses), 9,10 our findings encourage broader cognitive screening for older patients in the ED.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation